Vaccinations among Italian adolescents: Knowledge, attitude and behavior. Issue 7 (3rd July 2018) - Pelullo, Concetta Paola; Di Giuseppe, Gabriella
ABSTRACT: This study evaluates knowledge, attitudes and behaviors of adolescents regarding vaccinations. A cross-sectional study was conducted among a sample of 771 adolescents, aged 11 to 18 selected from a random sample of 5 public schools, in the period between March and May 2017, in the geographical area of Naples. A self-administered questionnaire was used to seek information about: 1) socio-demographic characteristics; 2) knowledge of vaccine-preventable diseases; 3) attitudes towards vaccinations; 4) behavior regarding vaccinations. 57.2% had a fair/satisfactory knowledge of vaccine-preventable diseases. This knowledge was significantly higher in those who had at least one graduated parent, those who had received information about the vaccines from physicians and those who needed additional information about the vaccines. With regards to attitude, 41.3% of adolescents had a very favorable attitude by responding 9 or 10 towards the utility of vaccines in preventing diseases. This was significantly associated with the usefulness of information received about vaccinations and with age of respondents. Regarding vaccination decisions, 47.2% believed that adolescents should make vaccination decisions for themselves. These results highlight the need to implement educational interventions to improve adolescents' understanding of vaccinations so that they are more informed in decisions regarding their health.